MENGURAI PROBLEMATIKA PEMBELAJARAN AKIDAH (Integrasi Cooperative Learning dengan Epistimologi Abid Al-Jabiri) - Winarto Eka Wahyudi (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
The process of Islamic religious education in schools has so far been centered on teaching materials. The materials have a varied segmentation of discussion, especially in the aspects of aqidah, ritual, akhlaq, history and so on. The values of Islamic teachings contained in teaching materials are not only related to both empirical and concrete aspects of knowledge. There are also the ones dealing with the abstract and unreasonable aspects. For example in the aqidah subject matter, there are discussions about belief in God, angels, the hereafter and so on. In this paper, the writer experimented with a learning method that integrates the cooperative learning approach with the Abid al-Jabiri's epistimological foundations. On this stand, the aqidah material in educational institutions is expected to run effectively on the one hand, and not to reduce the fundamental values of Islamic teachings on the other hand.Keywords: Aqidah learning, Coperative learning, Abid al-Jabiri